The Right to Self-determination in the Light of International Legal Issues and the Dissolution of Yugoslavia - Bartul Marušić (Studia Polensia, 2017)
The right to self-determination of peoples is one of the most controversial concepts in public international law. Also, this concept is not only legal, but also philosophical, and also pertains to political science, sociology and entails various issues and repercussions. Therefore, its analysis should be approached in detail, gradually and with an interdisciplinary approach in order to comprehend the various important aspects of the concept that leads toward the answer to the following question - Is the self- determination of peoples a principle or a right and what else in involved here? Is this right jus cogens de facto and de jure or is it conditioned by the organic other rules of contemporary international order? This primarily refers to the cogent ban of breaching the territorial integrity of existing states and jeopardizing international peace and stability as proclaimed in the Charter of the United Nations. This entails a consideration of the principle of uti possidetis and its roots, as well as secession, the most common consequence of the affirmative exercising of the right to self-determination of peoples. Also on the continuation and dissolution of states, mostly federal, which is necessary for an analysis whether or not there are any material differences in relation to secession, which is also neither permitted nor prohibited. The author here will interpret our closest known case (one still recent) the breakup of the former Yugoslavia, which was a modern precedent for a federal state and has reverberation in current events like those in the Ukraine. In order to have a more complete impression of law, policy and various interests will also make mention of the constitutionality of peoples, minorities and their rights through a variety of documents and the opinions of scholars and also concepts concerning the nation and state recognition. There is no consensus whether it is a constitutive or declaratory act by third countries and the international community. In order to avoid a worst case scenario, the acceptance of the legal “status quo”, it should be openly debated in order to avoid political and public diversions or distractions that hide interests which are either contrary to the spirit of the United Nations or, on the other hand, legitimately opposed to each other.